Self-Reported Race/Ethnicity Is Not Associated with Abnormal Semen Parameters after Accounting for Body Mass Index and Socioeconomic Status. Issue 1 (3rd July 2022) - Hudnall, Matthew; Goyette, Bailey; Ambulkar, Siddhant; Dubin, Justin; Pham, Minh; Lai, Jeremy; Fantus, Richard; Wren, James; Bennett, Nelson; Brannigan, Robert; Murphy, Adam; Halpern, Joshua
Abstract : Purpose: We evaluated whether consideration of body mass index (BMI) and socioeconomic status alters the reported association between race/ethnicity and abnormal semen parameters. Materials and Methods: We conducted a retrospective review of all men who underwent semen analysis (SA) for fertility evaluation at an integrated academic health care system from 2002 to 2021. Men were excluded if they had a diagnosis of Klinefelter's syndrome, history of varicocele, prior testicular surgery, prior history of chemotherapy or radiation for cancer, or prior testosterone-modulating medication use. Chi-square and Kruskal-Wallis tests were used to analyze categorical and continuous variables across self-reported racial groups, respectively. Logistic regression was used to evaluate the association between race and abnormal semen parameters according to WHO 2010 criteria, controlling for potential confounders. Results: Among 2, 750 men meeting inclusion criteria, 2, 037 (74.1%) identified as White Non-Hispanic, 207 (7.5%) as Black Non-Hispanic, 245 (8.9%) as Hispanic and 261 (9.5%) as Asian. Median age was 35 years (IQR 32–40). Black men had an older median age (37 years, IQR 33–42, p=0.002) than other groups at the time of index SA. While Black men had higher odds of abnormal sperm concentration (OR 1.46, 95% CI 1.06–2.02, p=0.02) and abnormal total motile sperm count (OR 1.65, 95% CI 1.21–2.25, p=0.001) compared to other men after adjusting for age alone, the association of race with abnormal semen parameters was rendered insignificant with the progressive inclusion of BMI, insurance status and neighborhood income as covariates. Conclusions: In men undergoing SA for fertility evaluation, we did not see evidence of an association between race/ethnicity and abnormal semen parameters after controlling for BMI, insurance status and neighborhood income.